Host Status of Endophyte-Infected and Noninfected Tall Fescue Grass to Meloidogyne spp. - Nyczepir, A. P. (The Society of Nematologists, 2010)
Tall fescue grass cultivars with or without endophytes were evaluated for their susceptibility to Meloidogyne incognita in the greenhouse. Tall fescue cultivars evaluated included, i) wild-type Jesup (E+, ergot-producing endophyte present), ii) endophyte-free Jesup (E-, no endophyte present), iii) Jesup (Max-Q, non-ergot producing endophyte) and iv) Georgia 5 (E+). Peach was included as the control. Peach supported greater (P ≤ 0.05) reproduction of M. incognita than all tall fescue cultivars. Differences in reproduction were not detected among the tall fescue cultivars and all cultivars were rated as either poor or nonhosts for M. incognita. Suppression of M. incognita reproduction was not influenced by endophyte status. In two other greenhouse experiments, host susceptibility of tall fescue grasses to two M. incognita isolates (BY-peach isolate and GA-peach isolate) did not appear to be related to fungal endophyte strain [i.e., Jesup (Max-Q; nontoxic endophyte strain) vs. Bulldog 51 (toxic endophyte strain)]. Host status of tall fescue varied with species of root-knot nematode. Jesup (Max-Q) was rated as a nonhost for M. incognita (BY-peach isolate and GA-peach isolate) and M. hapla, a poor host for M. javanica and a good host for M. arenaria. Bulldog 51 tall fescue was also a good host for M. arenaria and M. javanica, but not M. incognita. Jesup (Max-Q) tall fescue may have potential as a preplant control strategy for M. incognita and M. hapla in southeastern and northeastern United States, respectively.